Download presentation

Presentation is loading. Please wait.

Published byMalcolm Melton Modified over 5 years ago

1
5.3 – Solving Quadratic Equations by Factoring

2
Ex. 1 Solve y = x 2 + 5x + 6 by factoring.

3
x 2 + 5x + 6 = y

4
Ex. 1 Solve y = x 2 + 5x + 6 by factoring. x 2 + 5x + 6 = y x 2 + 5x + 6 = 0

5
Ex. 1 Solve y = x 2 + 5x + 6 by factoring. x 2 + 5x + 6 = y x 2 + 5x + 6 = 0 (x )(x ) = 0

6
Ex. 1 Solve y = x 2 + 5x + 6 by factoring. x 2 + 5x + 6 = y x 2 + 5x + 6 = 0 (x )(x ) = 0 (x + 2)(x + 3) = 0

7
Ex. 1 Solve y = x 2 + 5x + 6 by factoring. x 2 + 5x + 6 = y x 2 + 5x + 6 = 0 (x )(x ) = 0 (x + 2)(x + 3) = 0

8
Ex. 1 Solve y = x 2 + 5x + 6 by factoring. x 2 + 5x + 6 = y x 2 + 5x + 6 = 0 (x )(x ) = 0 (x + 2)(x + 3) = 0 x + 2 = 0

9
Ex. 1 Solve y = x 2 + 5x + 6 by factoring. x 2 + 5x + 6 = y x 2 + 5x + 6 = 0 (x )(x ) = 0 (x + 2)(x + 3) = 0 x + 2 = 0

10
Ex. 1 Solve y = x 2 + 5x + 6 by factoring. x 2 + 5x + 6 = y x 2 + 5x + 6 = 0 (x )(x ) = 0 (x + 2)(x + 3) = 0 x + 2 = 0ORx + 3 = 0

11
Ex. 1 Solve y = x 2 + 5x + 6 by factoring. x 2 + 5x + 6 = y x 2 + 5x + 6 = 0 (x )(x ) = 0 (x + 2)(x + 3) = 0 x + 2 = 0ORx + 3 = 0 -2 -2

12
Ex. 1 Solve y = x 2 + 5x + 6 by factoring. x 2 + 5x + 6 = y x 2 + 5x + 6 = 0 (x )(x ) = 0 (x + 2)(x + 3) = 0 x + 2 = 0ORx + 3 = 0 -2 -2 x = -2

13
Ex. 1 Solve y = x 2 + 5x + 6 by factoring. x 2 + 5x + 6 = y x 2 + 5x + 6 = 0 (x )(x ) = 0 (x + 2)(x + 3) = 0 x + 2 = 0ORx + 3 = 0 -2 -2 -3 -3 x = -2

14
Ex. 1 Solve y = x 2 + 5x + 6 by factoring. x 2 + 5x + 6 = y x 2 + 5x + 6 = 0 (x )(x ) = 0 (x + 2)(x + 3) = 0 x + 2 = 0ORx + 3 = 0 -2 -2 -3 -3 x = -2 OR x = -3

15
Ex. 2 Solve x 2 = 6x by factoring.

16
x 2 = 6x

17
Ex. 2 Solve x 2 = 6x by factoring. x 2 = 6x -6x

18
Ex. 2 Solve x 2 = 6x by factoring. x 2 = 6x -6x x 2 – 6x = 0

19
Ex. 2 Solve x 2 = 6x by factoring. x 2 = 6x -6x x 2 – 6x = 0

20
Ex. 2 Solve x 2 = 6x by factoring. x 2 = 6x -6x x 2 – 6x = 0 x(x – 6) = 0

21
Ex. 2 Solve x 2 = 6x by factoring. x 2 = 6x -6x x 2 – 6x = 0 x(x – 6) = 0 x = 0

22
Ex. 2 Solve x 2 = 6x by factoring. x 2 = 6x -6x x 2 – 6x = 0 x(x – 6) = 0 x = 0

23
Ex. 2 Solve x 2 = 6x by factoring. x 2 = 6x -6x x 2 – 6x = 0 x(x – 6) = 0 x = 0ORx – 6 = 0

24
Ex. 2 Solve x 2 = 6x by factoring. x 2 = 6x -6x x 2 – 6x = 0 x(x – 6) = 0 x = 0ORx – 6 = 0 x = 0

25
Ex. 2 Solve x 2 = 6x by factoring. x 2 = 6x -6x x 2 – 6x = 0 x(x – 6) = 0 x = 0ORx – 6 = 0 +6 +6 x = 0

26
Ex. 2 Solve x 2 = 6x by factoring. x 2 = 6x -6x x 2 – 6x = 0 x(x – 6) = 0 x = 0ORx – 6 = 0 +6 +6 x = 0OR x = 6

27
Ex. 3 Write a quadratic equation with roots 4 and -5. Write the equation in the form ax 2 + bx + c = 0, where a, b, and c are integers.

28
Ex. 3 Write a quadratic equation with roots 4 and -5. Write the equation in the form ax 2 + bx + c = 0, where a, b, and c are integers. x = 4x = -5

29
Ex. 3 Write a quadratic equation with roots 4 and -5. Write the equation in the form ax 2 + bx + c = 0, where a, b, and c are integers. x = 4x = -5 -4 -4+5 +5

30
Ex. 3 Write a quadratic equation with roots 4 and -5. Write the equation in the form ax 2 + bx + c = 0, where a, b, and c are integers. x = 4x = -5 -4 -4+5 +5 x – 4 = 0 x + 5 = 0

31
Ex. 3 Write a quadratic equation with roots 4 and -5. Write the equation in the form ax 2 + bx + c = 0, where a, b, and c are integers. x = 4x = -5 -4 -4+5 +5 x – 4 = 0 x + 5 = 0 (x – 4)(x + 5) = 0

32
Ex. 3 Write a quadratic equation with roots 4 and -5. Write the equation in the form ax 2 + bx + c = 0, where a, b, and c are integers. x = 4x = -5 -4 -4+5 +5 x – 4 = 0 x + 5 = 0 (x – 4)(x + 5) = 0 x 2 + 5x – 4x – 20 = 0

33
Ex. 3 Write a quadratic equation with roots 4 and -5. Write the equation in the form ax 2 + bx + c = 0, where a, b, and c are integers. x = 4x = -5 -4 -4+5 +5 x – 4 = 0 x + 5 = 0 (x – 4)(x + 5) = 0 x 2 + 5x – 4x – 20 = 0 x 2 + x – 20 = 0

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google